Selexipag in patients with pulmonary arterial hypertension associated with connective tissue disease (PAH‐CTD): Real‐world experience from EXPOSURE - Sean Gaine; Pilar Escribano‐Subias; Audrey Muller; Catarina C. Fernandes; Martina Fontana; Tatiana Remenova; Stefan Söderberg; Tobias J. Lange (Pulmonary Circulation, 2024)
Abstract Selexipag is indicated for the treatment of pulmonary arterial hypertension (PAH), including PAH associated with connective tissue disease (CTD), and further insights into the management of selexipag‐treated PAH‐CTD patients in clinical settings are needed. These analyses of the ongoing, multicenter, prospective EXPOSURE (EUPAS19085) study describe characteristics, treatment patterns, tolerability, and outcomes of PAH‐CTD patients initiating selexipag in Europe/Canada. All analyses were descriptive, with idiopathic PAH patients who typically display better prognosis included for context. Six hundred ninety‐eight selexipag‐treated patients had follow‐up information; 178 (26%) had PAH‐CTD. The median age was 68 years, patients were predominantly female (88%), and with WHO functional class III symptoms (63%); the median time since diagnosis was 1.7 years. There were 5% patients at low, 25% intermediate‐low, 40% intermediate‐high, and 30% high risk of 1‐year mortality, according to the ESC/ERS 4‐strata risk score. Most (80%) initiated selexipag as a triple oral therapy, and most of these (62%) remained on triple therapy 6 months post‐baseline. Over a median (Q1−Q3) selexipag exposure period of 8.6 (2.5−17.2) months, 79 (44%) patients discontinued selexipag; 36 (20%) due to tolerability/adverse events. Sixty (34%) patients were hospitalized at least once; 120 hospitalizations occurred, with 49 (48%) deemed PAH‐related. Survival at 1 year was 85%, and at 2 years was 71%; 29 (16%) patients died. These results describe the use of combination therapy with selexipag for patients with PAH‐CTD. These findings suggest an opportunity to optimize the benefits of selexipag among patients with PAH‐CTD by moving from escalating after years in response to clinical deterioration to escalating sooner to prevent clinical deterioration.